The relationship between students’ english background knowledge and their oral proficiency level in Readings and Conversation I course of the Bachelor of Arts in English with Emphasis in Teaching in the Foreign Language Department at the University of El Salvador semester II, 2017 - Díaz Cortez, Alejandro Antonio; Rodríguez Escoto, Efraín Arturo (2024)
The research was held with students of the course Readings and Conversation I from the Bachelor of Arts in English with Emphasis in Teaching in the Foreign Language Department at the University of El Salvador semester II, 2017. This research is descriptive since the researchers describe characteristics of the population or phenomenon that was studied in order to determine if there exists a relation between English background knowledge and their English Oral Proficiency. Regarding the communicative competences this research also presents information that can help to know if it is needed to set linguistic knowledge requirements for future students who want to apply to study the major in English Teaching in the Foreign Language Department at UES.